(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
This article provides a scientific analysis of histological changes in the pancreas in diabetes mellitus, with particular emphasis on the degeneration of the Islets of Langerhans. Diabetes mellitus, especially type 1, is characterized by autoimmune destruction of β-cells, islet atrophy, inflammatory infiltration, and fibrotic changes. In type 2 diabetes, amyloid deposition and progressive functional impairment are observed. These alterations lead to reduced insulin secretion and severe metabolic disturbances in the organism. The findings confirm that structural and functional damage of the Islets of Langerhans represents a central mechanism in the pathogenesis of diabetes mellitus.